Maternal Mental Well-Being and Infant Feeding Outcomes: A Systematic Review and Meta-analysis - Eri Kurniasari; Safira Mauliyatul Chusna; Atik Farokah; Britania Laila Nanda; Wafa Aulia Maharani; Salsabila Fitriana; Zelin Patarena Dawi Pramesti (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Maternal mental well-being is a crucial determinant of infant feeding outcomes. Psychological conditions such as postpartum depression, anxiety, and stress may influence a mother’s ability and motivation to initiate or sustain breastfeeding. However, the direction and magnitude of this association remain unclear. Objective : This systematic review and meta-analysis aimed to assess the association between maternal mental well-being and infant feeding outcomes, including exclusive breastfeeding practices. Research Methods/ Implementation Methods : A comprehensive literature search was conducted in Scopus, ScienceDirect, and PubMed databases for studies published between 2015-2025. Both observational and interventional studies examining maternal mental health and infant feeding outcomes were included. Data were synthesized using a random-effects model following PRISMA guidelines. Results : Three studies met the inclusion criteria and were included in the meta-analysis. The pooled odds ratio indicated no statistically significant association between maternal mental well-being and infant feeding outcomes (OR = 0.61; 95% CI = 0.18–2.00; p = 0.41). Considerable heterogeneity was observed among studies (I² = 87%), which may be attributed to variations in study design, population characteristics, and measurement instruments Conclusion/Lesson Learned : Although several individual studies suggest that poor maternal mental health may adversely affect breastfeeding and other infant feeding practices, the pooled results did not reveal a significant association. The high heterogeneity highlights the need for future longitudinal studies with standardized assessments of maternal mental well-being and infant feeding behaviors.